Utilization of Dairy Scum Waste as a Feedstock for Biodiesel Production via Different Heating Sources for Catalytic Transesterification - Mohd Johari, S.A. (John Wiley and Sons Inc, 2022)
The increasing demand of the world energy consumption has made it necessary to shift energy technologies toward renewable energy sources. The sustainability of feedstock can be maintained when utilizing feedstock from waste sources, such as dairy waste, food waste, and others. Dairy waste is one of the cheapest sources available. The compositions of dairy waste scum, including free fatty acids (8â10 ), triglycerides (more than 80 in dry bases), and fats around 60 , which have the potential to be used as the feedstock for biodiesel production in the presence of certain catalysts. To ensure more sustainability, the catalyst should be derived from waste (e.g., eggshells and cow bones) that consists of calcium oxide, which can then be used to catalyze the transesterification of dairy waste. This review emphasizes the current production of dairy waste globally and the potential of the waste and other types of organic waste as feedstock for biodiesel production, as well as determines the optimum reaction conditions for high-quality biodiesel production. Â© 2022 Wiley-VCH GmbH.